The Literature review: Investigasi Perbandingan Antioksidan pada Tanaman Obat Herbal di Pulau Jawa dengan Spektrofotometri UV-Vis dan Metode DPPH (2,2-difenil-1-pikrilhidrazil) - Sebayang , Madame Marselly; Mierza , Vriezka (Journal of Pharmaceutical and Sciences, 2026)
Due to environmental changes and pollution due to free radicals, interest in alternative medicine is increasing, especially on the island of Java. Natural health solutions are increasingly needed, which is what prompted this research. We measured the concentration of antioxidant compounds using the UV-Vis spectrophotometric method and the free radical scavenging capacity of plant extracts using the DPPH method. Using the 2,2-diphenyl-1-picrylhydrazyl (DPPH) and UV-Vis spectrophotometric methods with IC50 value determination, this article aims to investigate and compare potential herbal plants found on the island of Java. This research was carried out using a literature review method by considering inclusion and exclusion criteria with keywords such as antioxidants, herbal medicinal plants, UV-Vis spectrophotometry, and DPPH method. The results showed that the plant species studied had different antioxidant activities. Some herbs have high levels of antioxidants, so they may be used as natural health supplements. Additionally, this study emphasizes how important it is to use accurate analytical methods to evaluate antioxidant content. To provide a comprehensive picture of the antioxidant potential of each plant, UV-Vis spectrophotometry and DPPH methods work together. The results show that this study identified several herbal plants on the island of Java that have high levels of antioxidants. These plants can be used to develop herbal-based health products. To carry out a comparative evaluation of antioxidant content, the UV-Vis and DPPH spectrophotometric methods were proven to be effective. This discovery can be the basis for further research and development of more effective and useful herbal health products.